EXTH-40. DIPGS SUPPRESS THE EFFICACY OF T CELL THERAPIES THROUGH DYSFUNCTIONAL IMMUNE SYNAPSE FORMATION. (14th November 2022) - Ibanez, Jorge; Houke, Haley; Elayan, Abdul; Ocasio-Adorno, Jennifer; Hebbar, Nikhil; Velasquez, Paulina; Baker, Suzanne; Krenciute, Giedre
Abstract: Diffuse intrinsic pontine gliomas (DIPGs) are highly lethal pediatric brain tumors. Thus, there is an urgent need for novel therapeutics. While chimeric antigen receptor (CAR) T-cell therapy has the potential to meet this need and early phase clinical studies with CAR T cells have shown safety and some efficacy, additional studies are needed to understand the lack of efficacy of CAR T cells against DIPGs. The goal of this study was to identify CAR T cell efficacy limiting factors in DIPG setting. To study that, we focused on targeting GRP78, an endoplasmic reticulum chaperone protein that is broadly expressed on the cell surface of DIPGs. We generated GRP78-specific CAR T cells and compared their effector function against U87 glioma and the patient-derived DIPG007 cell line. Despite that GRP78-CAR T cells recognize and kill U87 and DIPG007 tumor cells in vitro, they were only effective against U87 in vivo. In addition, in vitro cytokine production and T cell proliferation were heavily diminished in DIPG007, compared to U87. For full activation, T cells require a cell-to-cell interaction and the formation of a highly organized structure called immune synapse (IS). Experiments using confocal microscopy showed that the IS quality, measured as lytic granule accumulation and cytoskeleton organization at the IS, was impaired in DIPG007 when compared to U87. This dysfunctional IS correlated with poor T cell activation (calcium flux) as determined by live cell imaging. We observed the same dysfunctional IS formation regardless of CAR T cell specificity and targeted antigen expression level, indicating that the suppressive effect is DIPG tumor mediated. In summary, we demonstrate that DIPGs suppress CAR T cell effector function through dysfunctional IS formation. We are now testing genetic engineering approaches directed at improving IS formation to overcome the suppressive effects of DIPGs.